Non-contact real-time water and brine concentration monitoring in crude oil based on multi-variable analysis of microwave resonators. (June 2021) - Baghelani, Masoud; Hosseini, Navid; Daneshmand, Mojgan
Abstract: Non-contact analysis of multi-component two-phase mixtures including immiscible liquids and solutions simultaneously by a single sensing structure with a wide dynamic range is addressed in this paper. The mixture of interest in this work comprises oil and water with variable salinity extended from 0 to 35 (g/kg). As low overall concentration of water as 1% is successfully measured through the innovative measurement procedure of microwave split-ring resonators. The enabling multi-variable analysis technique in this work is based on employing multiple features which are the frequency shifts of various harmonics of the resonator instead of just using one resonance frequency as the traditional microwave resonators-based sensors. Higher numbers of features provide information for the development of more equations enabling analyzing of more complex mixtures. Experimental results verify the developed approach with the resulting low Mean-Square- Errors in the range of 10 −5 for the water-brine-oil mixture.